An improved real-time temperature control for pulsed laser cutting of non-oriented electrical steel. (April 2021) - Nguyen, Dinh-Tu; Ho, Jeng-Rong; Tung, Pi-Cheng; Lin, Chih-Kuang
Graphical abstract: Highlights: An improved real-time temperature control with FGS is developed for laser cutting. Working temperature and kerf width vary significantly under open loop control. FGS controller exhibits a better performance than conventional PID controller. FGS control effectively reduces over-burning and produces finer and uniform kerf. Kerf width is linearly correlated with set-point temperature in FGS control. Abstract: An improved method based on fuzzy gain scheduling (FGS) control is developed in this study to tune the PID parameters and precisely control the working temperature in situ during laser cutting of non-oriented electrical steel sheets. Experiments on laser cutting of thin electrical steel sheets are performed to compare the cutting quality of kerf features using an open loop controller with a constant power, a conventional PID controller, and the proposed FGS controller. An unstable and inconsistent cutting quality of kerf with a larger heat affected zone (HAZ) and dross attachment is observed under open loop control due to a significant variation of working temperature and kerf width along the cutting path. The FGS controller shows better cutting performance and tracking response than the conventional PID controller by reducing the settling time as well as enhancing the control stability in the steady period. A better quality of finer and uniform kerf width with parallel kerf edges of a smaller HAZ and dross attachment are thus produced by the improved FGS control through real-time tuning of control parameters. Finally, the average kerf width is well correlated with the set-point temperature in FGS control by a linear equation.